Cerebellar Vermis Anomaly in ADHD - J Gordon Millichap (Pediatric Neurology Briefs, 1998)
Cerebellar and vermal volumes were measured by quantitative MRI studies in 46 right-handed boys with attention deficit hyperactivity disorder (ADHD) and 47 matched healthy controls, and results were analyzed at the Child Psychiatry Branch, National Institute of Mental Health, Bethesda, MD.